THE ROLE OF TECHNOLOGY IN TEACHING GERMAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The use of technology in language instruction has drastically changed the way that languages are taught and acquired in recent years. The use of digital tools and platforms is particularly advantageous for German, a language that is spoken by millions of people globally. The benefits of using technology in German instruction, its effects on student learning, and the different resources that teachers and students are using more and more are all covered in this essay. Surveys, interviews, and a thorough literature study offer insights on how internet resources, multimedia technologies, and mobile apps improve the educational process. Findings suggest that when used appropriately, technology boosts engagement, enhances linguistic skills, and fosters deeper understanding of cultural context in language learning.